The effect of comprehensive income disclosure on capital costs, earnings quality, and profitability - Akbar Abdi Negara; Luciana Spica Almilia Almilia (Universitas Hayam Wuruk Perbanas, 2015)
This study was induced by the change from SFAS 2009 to SFAS 2012. One of the changes contained in SFAS No. 1 states that comprehensive income statement is an additional component of other comprehensive income. The study aims to determine whether there are differences in the capital cost, earnings quality, and profitability be-tween companies that report comprehensive income statement and companies that do not report comprehensive income statement. The sample of the study consists of 120 manu-facturing companies listed on the Indonesian Stock Exchange (BEI) in 2012. It uses Statistical test that is the Mann Whitney test due to the data, which were not normally distributed. The results of the research indicate that the significance level of capital cost variable is 0.038, earnings quality variable is 0.192, and profitability variable is 0.029. Therefore, it can be concluded that there are differences in the level of capital cost and profitability between companies that report comprehensive statements and companies that do not report comprehensive income statement. On the contrary, there is no differ-ence in the level of earnings quality between companies that report comprehensive in-come statement and companies that do not report comprehensive income statement.